Pertumbuhan dan Produktivitas Jagung Manis pada Beberapa Sistem Tanam - Wentasari, Risa (Akta Agrosia, 2016)
The purpose of this study was to determine the growth and productivity of sweet corn on a Single Row, Double Row, Row Twins and Twins Seed planting system. This study was conducted in an experimental garden of Politeknik Negeri Lampung, Hajimena South Lampung, in July-September, 2015. This study is based on randomized block design with one factor cropping system consists of 4 treatment ie : Single Row (SR) (20cm x 75cm), Double Row (DR) (20cm x 20cm x 80 cm), Twins Row (TR) (20cm x 10cm x 80 cm) , and TwinsSeed (TS) with plant spacing (40cm x 75cm two seed in one planting hole). Parameter observational studies high plants (cm), leaf number (cm), diameter (cm), lebar daun (cm) and long leaf (cm) and productivity  (ton/ ha). The data were analyzed using the F test at  1 % and 5 % level and than followed by test BNT.  The conclusion of this study were (1) planting system gives a response was not significantly different in stem diameter and leaf length, the difference is shown in plant height, number of leaves and leaf width, 2) There is a significant differences in the productivity cropping systems. Twins Row cropping systems have different productivity with a Single Row planting system, Double Row, Twins Seed and (3) Average Twins Seed planting system showed the highest productivity of 39.42 ton/ha.